The Role Of Digital Banking In Taking The Opportunities And Challenges Of Sharia Banks In The Digital Era - Sutikno Sutikno; Nursaman Nursaman; Muliyat Muliyat (Institute of Computer Science (IOCS), 2022)
Rapid technological developments gave birth to digital banking or better known as digital banking. How to prepare Islamic banks in taking opportunities and challenges in the digital era. sharia banking in Tangerang city in facing the digital era. This study uses a qualitative method with a phenomenological approach to find the opportunities and challenges of Islamic banks in the digital banking era. Data collected through observation, interviews, and documentation. The results of this study found that there are opportunities and challenges that faced by Islamic banks in the digital era, namely; 1) the convenience felt after the emergence of digital banking begins with the convenience of transactions without having to go to a direct bank. 2) digital banking is a sharia concept based on Islamic religious teachings which is far from usury. 3) accelerates the activities of Islamic banks in Malay This is the customer. The challenges experienced by Islamic banks in this digital banking era are due to the high level of competition against conventional banks and the delay in internet networks that are always lagging behind